The effects of visionary leadership on organizational development in an emerging philanthropic foundation - Lisdawati Muda (Lentera Negeri, 2026)
This study examines how visionary leadership is enacted and translated into organizational development within the Dhia Tasmirah Andrizal Foundation (YDTA), an educational-based non-profit organization. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document analysis involving the foundation’s governing bodies and leaders of affiliated educational institutions. The findings indicate that visionary leadership at YDTA is not practiced primarily as a top-down articulation of a future-oriented vision. Rather, the vision is translated into organizational development through a multilayered leadership process in which foundation leaders and educational-unit leaders collectively interpret priorities, coordinate institutional initiatives, and adapt strategic decisions to changing organizational and societal needs. This finding reveals a tension with conventional conceptualizations of visionary leadership that emphasize the leader as the primary source and driver of organizational vision. At YDTA, the effectiveness of vision appears to depend less on the personal articulation of a compelling future and more on its institutionalization through distributed leadership, collaborative decision-making, and continuous adaptation across organizational levels. These practices were associated with the expansion of educational units, improvements in institutional quality, and increased student enrollment, while also strengthening organizational coordination and stakeholder engagement. The study therefore contributes an empirically grounded perspective on visionary leadership by showing how a future-oriented vision can become an organizational capability rather than remain an individual leadership attribute. The findings suggest that, in educational non-profit organizations, the sustainability of visionary leadership may depend on the organization’s capacity to distribute, interpret, and continuously enact the vision across institutional levels.